Microservices antipatterns and pitfalls : learning to avoid costly mistakes - Richards, Mark; Safari eBooks ([Place of publication not identified] : O'Reilly, 2016)
"Microservices is an increasingly popular architecture style that promotes scalability and ease of testing and deployment through small, highly distributed service components. It may sound like the correct architecture for your situation, but if you're new to microservices, how do you really know? Understanding microservices' pitfalls (practices that are never a good idea) and anti-patterns (practices that seem like a good idea, but aren't) is a good place to start. In this video, 20+ year software architecture veteran Mark Richards (IBM, CSC, etc.) doesn't just identify the pitfalls and anti-patterns of microservices, he shows you how to avoid them. You'll learn about service granularity estimation, database migration, microservices reporting, distributed transaction management, remote access latency, contract versioning, distributed logging, and much more."--Resource description page.
Title from title screen (viewed July 29, 2016).
Presenter, Mark Richards.
Keywords: Application software -- Development; Software architecture; Electronic books